Sugarcane bagasse as a partial replacement of fine aggregates in concrete / Nor Fadilah Mohamad ... [et al.] - Mohamad, Nor Fadilah; Hasbullah, Amran; Idris, Nazirul Hasyir; Razali, Rosimawati; Abd Khodir, Aiman Zuhair
This study was carried out pa11ial replacement of aggregates in concrete by sugarcane bagasse in order to reduce the industrial waste by saving the aggregates that is more environmental friendly. The waste utilization can helps to reduce the pollution in the world. Due to the increase in consumption of sugarcane, the sugarcane bagasse waste was increase and the waste is disposed in the landfills and now becoming the environmental problem. Many agricultural waste materials are used as replacement alternative for cement, fine aggregate and coarse aggregate. Sugarcane bagasse is one of the wastes that can use in the construction. Aluminium ion and silica are the element that contain in the sugarcane bagasse that suitable to partially replace of aggregates in the concrete. By using this waste, it can control the adverse effect of pollution because of disposal waste. In addition, it also can reduce the economic cost of construction because use of the waste material from the sugar industry. The concrete more strength because, the silica that present in the bagasse react with the component of cement during the hydration and impart additional properties such as corrosion resistance and chloride resistance. In this study, the sugarcane bagasse has been partially replaced in the ratio of 5% and 8% by volume of fine aggregates in concrete. The concrete was taken a test such as compression test and water absorptivity test. The concrete was moulding in the size of 100mm cube size. The concrete was curing for 7, 14 and 28 days in the open area.